To be Takei [videorecording (DVD)] - Kroot, Jennifer M.; Takei, George, 1937-; Takei, Brad; Nimoy, Leonard; Shatner, William; Nichols, Nichelle; Koenig, Walter, 1936-
The legendary George Takei has blazed his own trail while conquering new frontiers with a beaming trademark grin. Take a hilarious, entertaining, and moving look at the many roles played by eclectic 77-year-old actor/activist George Takei. The film offers unprecedented access to the daily life of George and his husband/business partner, Brad Takei, and chronicles his fascinating personal journey from Japanese American internment camp to his iconic and groundbreaking role as Sulu on Star Trek, and his rise as a pop culture icon.